Building Family Security to End Child Marriage - Pinky Saptandari (Yayasan Jurnal Perempuan, 2016)
Child-marriage is easily found in most area in Indonesia and is second highest in ASEAN countries after Cambodia. Complexity of child-marriage roots in cultural tradition triggered by religious interpretation. However such facts being worsen as affected by regulations that legalized child-marriage. The soaring of child-marriage provides picture of the weakness of women and young girls in the family and society within dominance patriarchy ideology. Considering such ideology, gender inequality causes women and young girls having minimum access and bargaining position in the decision-making process. When this happens the rights of young girls are difficult to fulfill as can be seen in the fact of high-reaching child-marriage. In Kabupaten Sumenep, East Java, for example, under-age marriage reached 42,5% in 2015. Such complexity needs simultaneous and comprehensive efforts from national level to the desa (village) level which involving related stakesholder in the society. In this paper, I will develop opportunities and strategic measures in counteract child-marriage through the integratization of regulation such as Undangundang no. 6/2014 on the Desa as an entrance to build gender equality, women empowerment and child-protection to campaign against child-marriage.